2005
DOI: 10.1002/jccs.200500117
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Determination of Chemical Constituents in the Roots ofRhus JavanicaL. Var.Roxburghiana

Abstract: From the roots of Rhus javanica L. var. roxburghiana, totally thirty-seven known compounds have been isolated and identified. Their structures were elucidated based on their spectral analysis as well as comparison with authentic samples. These compounds were grouped to be fifteen triterpenoids, five steroids, two lignans, two flavonoids, nine phenolics, and four other aromatic derivatives. Their cytotoxicities toward two cell lines NUGC-3 and HONE-1 were also evaluated. zyl alcohol (31), 38 gallic acid (32), 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…1), gallic acid (1) (Lee, Chiou, Lee, & Kou, 2005), ethyl gallate (2) (Hussain, Modan, Shabbir, & Zaidi, 1979;Zhang, Chen, Pei, & Hua, 2001), 1-O-galloyl-b-D-glucopyranoside (3) (Kashiwada, Nonaka, & Nishioka, 1984), methyl brevifolin carboxylate (4) (Yao & Zuo, 1993), brevifolin (5) (Mahmoud, Sahar, & Irmgard, 1994;Sha, Liu, Wang, & Xu, 2000), corilagin (6) (Mahmoud et al, 1994;Sha et al 2000), ellagic acid (7) (Mahmoud et al, 1994) and 4-O-a-L-rhamnopyranosylellagic acid (8) (Yang et al, 1998), were determined by interpretation of their spectroscopic data (see supplementary data) as well as by comparison with reported data. The structures were further supported by co-TLC with authentic compound samples or hydrolysis followed by co-TLC with authentic compound samples (see supplementary data).…”
Section: Isolation and Structure Determinationmentioning
confidence: 99%
“…1), gallic acid (1) (Lee, Chiou, Lee, & Kou, 2005), ethyl gallate (2) (Hussain, Modan, Shabbir, & Zaidi, 1979;Zhang, Chen, Pei, & Hua, 2001), 1-O-galloyl-b-D-glucopyranoside (3) (Kashiwada, Nonaka, & Nishioka, 1984), methyl brevifolin carboxylate (4) (Yao & Zuo, 1993), brevifolin (5) (Mahmoud, Sahar, & Irmgard, 1994;Sha, Liu, Wang, & Xu, 2000), corilagin (6) (Mahmoud et al, 1994;Sha et al 2000), ellagic acid (7) (Mahmoud et al, 1994) and 4-O-a-L-rhamnopyranosylellagic acid (8) (Yang et al, 1998), were determined by interpretation of their spectroscopic data (see supplementary data) as well as by comparison with reported data. The structures were further supported by co-TLC with authentic compound samples or hydrolysis followed by co-TLC with authentic compound samples (see supplementary data).…”
Section: Isolation and Structure Determinationmentioning
confidence: 99%
“…These data, together with the presence of 15 carbon signals in the 13 C NMR spectrum (4 x C 4 , 2 x CH, 5 x CH 2 , 4 x CH 3 ) suggested that 9 was a sesquiterpene. By comparison of the spectroscopic data with those published in literature, compound 9 was identified as 2,6,10-bisabolatriene [16].…”
Section: Resultsmentioning
confidence: 81%
“…Medium polarity fractions (the ones eluted with hexane: AcOEt 9 : 1 to AcOEt 100%) seemed to concentrate the deterrent activity (most of them were active against more than one of the insect models). From the second fraction eluted with hex/AcOEt (8 : 2) (fraction number 6 in table 1; 0.45 g) which showed differential activity when tested against the insect models, the pentacyclic triterpene lupeol (1, 15 mg) (Burns et al 2000), and the sterols stigmasterol (2, 6 mg) (Kojima et al 1990;Kolak et al 2005), and stigmast-7-en-3-ol (3, 3.5 mg) (Kojima et al 1990;Lee et al 2005) were isolated (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%